PELATIHAN TEKNIK HIDROPONIK SEDERHANA UPAYA PENGEMBANGAN LAHAN TIDUR MENJADI LAHAN PRODUKTIF DI DESA KARANGREJA - Abdul Azis Husaini; Ninik Paryati; Neneng Lasmita Susanti (An-Nizam, 2023)
Land utilization for large industries is usually used as a form of large economic practices that involve a lot of production costs. But for a village, utilizing existing land will be a great help that does not require large costs. Utilizing simple land around the house or neighborhood will get many benefits, especially small cost benefits. Many residents have not been able to utilize the land around the environment to become productive land that produces profits. Therefore, the method used is to conduct training to residents who do not understand to utilize their narrow land into economically productive land with simple equipment. The result of the implementation of a simple hydroponic training program in an effort to develop idle land is that the head of Karangreja Village requested that hydroponics be made in the village as an example for the wider community who want to follow the example of hydroponics with the DFT method.